Exploring attitudes toward eating disorders among elite athlete support personnel. Issue 9 (1st July 2015) - McArdle, S.; Meade, M. M.; Moore, P.
Abstract : To date, little is known about the beliefs, attitudes, and experiences of athlete support personnel (ASP) working in elite sport toward disordered eating (DE) and eating disorders (EDs). This study seeks to explore this area of mental health, employing an attribution model of stigma as a conceptual lens. Interviews were undertaken with 14 service providers (seven males and seven females) working in high‐performance sport in Ireland. In contrast to previous research in the general population, findings revealed that sport‐based personnel, in the main, did not hold the individual responsible for the development of their eating disorder. The predominant emotional response of those who had worked with an athlete with a known or suspected eating disorder was anxiety and worry. In line with the findings of previous studies with other health professionals, negative views on the prognosis of those with EDs were expressed by the ASP. Furthermore, confidentiality was found to be a significant barrier to bringing athletes' disclosure of problematic eating or exercise behavior to the fore. The findings of this study add to the limited research exploring attitudes toward EDs in sport and highlights the importance of greater education and openness toward this particular mental health problem.